(untitled) (Baghdad Science Journal, 2012)
The present investigation was conducted to evaluate the effect of the crude extracts mixture of three plants (Tribulus terrestris, Phoenix dactylifera and Nasturtium officinale) on semen quality,sex hormones and reproductive performance of mature male mice. A group of 25 male mice given 150mg/kg/day of the powder of the plants mixture with the food for four weeks and another three groups of 25 animals each given intraperitoneal injection from each of the aqueous and ethanolic extracts with a doses 75, 150, and 300mg/kg/day for two weeks. A remarkable increase in sperm concentration and motility with a decreased abnormal morphology was obtained in the experimental groups. A significant increase in hormones level were recognized in most groups. The results of mating untreated females with treated males of the four experimental groups revealed a decreased gestation period and an increased litter size. The results showed a dose dependent pattern of activity and the effect of the extracts were enhanced with increasing the dose level. The ethanolic extract being the more effective extract in all parameters.